Implementation of Diabetes Self Management Education (DSME) Intervention On Glycemic Control with Diabetes Mellitus Type 2: A Systematic Review - Martopo, Nur Agung; Hidayatullah, M. Furqon; Syaifullah, Rony (Future Science, 2024)
Diabetes Mellitus is a metabolic condition commonly caused by deficiencies in insulin secretion or activity. Chronic non-communicable diseases (DM) have emerged as a significant health problem worldwide. By 2035, approximately 9% of the world's population will have type 2 diabetes mellitus (T2DM). Solutions are needed to address further management of T2DM, including education for comprehensive care that can be provided to people with type 2 DM through Diabetes Self Management Education (DSME). This study aims to determine how patients with type 2 diabetes mellitus can reduce their blood glucose levels by applying the Diabetes Self-Management Education (DSME) intervention. This systematic review followed the design and outcome stages' reporting item guidelines (PRISMA). Based on the Cochrane database, ScienceDirect, PubMed, and Scopus, 15,789 research articles used related keywords. The inclusion criteria were Type 2 Diabetes Mellitus patients, patients without severe symptoms or other complications, patients capable of self-care, studies published between 2017 and 2023 as the year of publication, full-text articles, and English-only publications. After the screening process, twelve research articles were obtained according to the inclusion criteria. The analysis method used was the descriptive method. The results of this review are described in narrative form. Diabetes Self Management Education (DSME) positively impacts monitoring blood glucose and HbA1c levels in patients with type 2 diabetes mellitus. It is practical to be implemented as a support program to improve diabetes management.